2017
DOI: 10.1094/cchem-05-17-0084-r
|View full text |Cite
|
Sign up to set email alerts
|

Gluten Aggregation Behavior in High‐Shear‐Based GlutoPeak Test: Impact of Flour Water Absorption and Strength

Abstract: Cereal Chem. 94(5):909-915Gluten aggregation behaviors of wheat flour were evaluated using a high-shear-based method with the GlutoPeak instrument and related to flour functional properties. GlutoPeak peak time (PT) and peak area (PA) were positively associated with gluten strength but negatively affected by farinograph absorption (FAB). GlutoPeak maximum torque (T max ) was highly positively (P < 0.001) correlated with FAB regardless of gluten strength. PT and PA increased with the decrease of FAB. This could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…( Table 3). These results and reports by others Wang et al, 2017) suggest that to compare samples GlutoPeak aggregation behavior they should be milled in the same way and have a narrow range in WA. The earlier mixing time is related to more rapid gluten development as the water can hydrate the finer particles more quickly and the higher torque could be related to the higher consistency of flours that have higher water absorption probably leading to a thicker slurry requiring increased energy to mix (Area) as noted by Fu, Wang, and Dupuis (2017).…”
Section: Effects Of Grinding On Glutopeak Gluten Aggregation Behaviorsupporting
confidence: 81%
See 3 more Smart Citations
“…( Table 3). These results and reports by others Wang et al, 2017) suggest that to compare samples GlutoPeak aggregation behavior they should be milled in the same way and have a narrow range in WA. The earlier mixing time is related to more rapid gluten development as the water can hydrate the finer particles more quickly and the higher torque could be related to the higher consistency of flours that have higher water absorption probably leading to a thicker slurry requiring increased energy to mix (Area) as noted by Fu, Wang, and Dupuis (2017).…”
Section: Effects Of Grinding On Glutopeak Gluten Aggregation Behaviorsupporting
confidence: 81%
“…Previous work on a much smaller sample size (n = 32) found a strong positive correlations between PMT-S with MPT and GI and a negative correlation with RBD (Sissons, 2016). Torque-WM was highly correlated to GP, WG and MPH and is not useful at predicting dough strength as noted previously (Marti et al, 2014;Sissons, 2016;Wang et al, 2017). To investigate this relationship further set 1 was evaluated with GlutoPeak and the aggregation behavior compared with 10 g mixograph parameters, gluten index and SDS sedimentation volume and SDSS/GP, tests commonly used in durum breeding programs.…”
Section: Comparison Of Glutopeak Test With Other Dough Testsmentioning
confidence: 60%
See 2 more Smart Citations
“…The GlutoPeak (Brabender, Duisburg) device examines gluten aggregation properties, using relatively small flour samples (8.5 g) and short analysis times (<3.0 min) (Fu et al, ; Karaduman et al, ; Lu & Seetharaman, ; Marti et al, ; Melnyk et al ; Wang, Dupuis, & Fu, ), and has been suggested for assessing the gluten strength of soft wheat flour doughs (Amoriello, Turfani, Galli, Mellara, & Carcea, ). Peak maximum time (PMT), maximum torque (BEM), torque before 15 s BEM (AM), torque after 15 s BEM (PM), and aggregation energy (AGG EN) parameters are obtained with the instrument.…”
Section: Resultsmentioning
confidence: 99%